PENGARUH PENGELOLAAN DANA ZAKAT PRODUKTIF TERHADAP PENDAPATAN USAHA MIKRO MASYARAKAT PADA LEMBAGA INISIATIF ZAKAT INDONESIA (IZI) SUMATERA UTARA - Rahmad Ridwan (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2018)
The productive zakat is zakat given to the poor in the form of business capital or another used for productive business which will improve the standard of living in the hopes of a mustahik will be muzakki if it can Use the property for his business. The purpose of this study is to analyze the influence of productive Zakat fund management against community micro-business revenues. The research approach used is a descriptive-quantitative research method. Research initiated by collecting quantitative data, which is tangible figures are then compiled systematically and processed with SPSS Statistics Version 20.0 program. The result of T test for the management of Productive Zakat Fund (X) on Community micro-business income (Y) shows the value of Sig 0.000 and T count indicates the value 18.189 means that the value of Sig is smaller than the probability value 0.05 (0.000 < 0.05) and T count Greater From T table (18.189 > 2.100), then the conclusion that can be taken is H0 in reject and Ha received. This means that the management of productive zakat funds is partially significant impact on the income of Microbusiness Mustahik at IZI Institute of North Sumatera Province.